Evidence-based of conjunctival COVID-19 positivity: An Italian experience: Gemelli Against COVID Group. Issue 6 (November 2021) - Savastano, Maria Cristina; Gambini, Gloria; Savastano, Alfonso; Falsini, Benedetto; De Vico, Umberto; Sanguinetti, Maurizio; Cattani, Paola; Marchetti, Simona; Larici, Anna Rita; Franceschi, Francesco; Santoliquido, Angelo; Moroni, Rossana; et al.
Background: The possible transmission of severe acute respiratory coronavirus 2 (SARS-CoV-2) by tears and conjunctiva is still debated. Methods: Main outcome was to investigate the agreement between nasopharyngeal swab (NPs) and conjunctival swabs (Cs) in patients with SARS-CoV-2 infection. We divided patients into four groups: (1) NPs and Cs both negative (C−NF−), (2) NPs positive and Cs negative (NFs+Cs−), (3) NPs negative and Cs positive (NFs−Cs+), and (4) NPs and Cs both positive (NFs−Cs+). The secondary outcomes were to correlate Cs results with systemic clinical parameters such as: oxygen saturation (SpO2 ), dyspnea degree (DP), radiologic pulmonary impairment based on chest radiography (XR) or computed tomography (CT), blood chemistry as D-Dimer (D-Dimer), fibrinogen, ferritin, lactate dehydrogenase (LDH), and C-reactive protein (C-RP). Results: A total of 100 conjunctival swabs in 50 patients with SARS-CoV-2 have been enrolled in this interventional clinical trials. Ocular signs (conjunctivitis) were present in five patients (10%). NPs and Cs highlighted a poor level of agreement (0.025; p = 0.404). Median SpO2 levels are the highest in the NF−C− group (98%) and the lowest (90%) in the group NF+C+ ( p = 0.001). Pulmonary impairment was statistically significantly different between NFs and Cs groups ( p = 0.019). Pulmonary impairment score increased from NFs−Cs− group (3.8 ± 3.9), to NFs+Cs+ group (6.7 ± 4.1). Intensive care unit patients showed higher COVID-19 Cs positivity in conjunctiva (12.5%) against hospitalized ones (5.8%). Conclusions: In patients hospitalized for SARS-CoV-2 the virus can be detected in conjunctival swab. Intensive care unit patients may reveal a higher COVID-19 presence in the conjunctiva. The most severe pulmonary impairment can be observed in NFs and Cs positivity. Trial registration: Clinicaltrials.gov registration. Ethical committee authorization: ID number: 0013008/20